2017
DOI: 10.1103/physrevlett.119.090602
|View full text |Cite
|
Sign up to set email alerts
|

Order and Symmetry Breaking in the Fluctuations of Driven Systems

Abstract: Dynamical phase transitions (DPTs) in the space of trajectories are one of the most intriguing phenomena of nonequilibrium physics, but their nature in realistic high-dimensional systems remains puzzling. Here we observe for the first time a DPT in the current vector statistics of an archetypal two-dimensional (2d) driven diffusive system, and characterize its properties using macroscopic fluctuation theory. The complex interplay among the external field, anisotropy and vector currents in 2d leads to a rich ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 68 publications
2
43
0
Order By: Relevance
“…Seeing the SCGF as a function of the state's parameters (or of the bias), this may be interpreted as a "dynamical phase transition," of the type seen in other contexts, see e.g. [52,53,54,55,56,57,58,59,60]. We explain why this occurs from hydrodynamic principles, and how this may connect with the breaking of Gaussianity found in nonlinear fluctuating hydrodynamics [61,47,62].…”
Section: Introductionmentioning
confidence: 73%
“…Seeing the SCGF as a function of the state's parameters (or of the bias), this may be interpreted as a "dynamical phase transition," of the type seen in other contexts, see e.g. [52,53,54,55,56,57,58,59,60]. We explain why this occurs from hydrodynamic principles, and how this may connect with the breaking of Gaussianity found in nonlinear fluctuating hydrodynamics [61,47,62].…”
Section: Introductionmentioning
confidence: 73%
“…The motivation for studying this model is that it shows a dynamical phase transition (DPT), that is, a sudden change in the way that fluctuations are created in the long-time limit, leading to singularities in large deviation functions, the nonequilibrium analogs of thermodynamic potentials [2]. Similar DPTs are found in interacting particle systems such as kinetically constrained models of glasses [3][4][5] and the exclusion process [6][7][8][9][10], which show DPTs in the integrated activity or current for some parameter values. In these and many other models, however, a DPT arises when taking the long-time limit in addition to a hydrodynamic or macroscopic limit [11][12][13][14], which is equivalent to a low-noise limit [15][16][17].…”
Section: Introductionmentioning
confidence: 87%
“…This system has been considered recently [37], where it was found that its large deviation function for current fluctuations in the direction of the driving exhibits a dynamical phase transition. For small λ, the system is in a homogeneous phase, while for large negative λ, the system phase separates, forming a traveling wave in the direction of the biased current.…”
mentioning
confidence: 99%